Porous carbon loaded titanium nitride synergistic platinum-titanium alloy catalyst and preparation method thereof

Through the coordinated combination of titanium nitride and platinum particles supported on the carbon support, the problem of inactivation of platinum catalysts in the prior art in the fuel cell environment is solved, and a significant improvement in high stability and activity is achieved.

CN119581574AActive Publication Date: 2025-03-07WUHAN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411673477.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Existing carbon-supported platinum catalysts are prone to inactivation in harsh fuel cell working environments and are difficult to simultaneously inhibit the migration, dissolution of platinum particles and the oxidation of carbon support.

Method used

The carbon support is loaded with high corrosion resistance titanium nitride material, and combined with platinum particles, the migration and dissolution of platinum particles are prevented through the interaction between titanium nitride and platinum particles, while enhancing the durability of the carbon support.

Benefits of technology

The stability and activity of the catalyst are significantly improved, and the redox properties of the catalyst can be basically not changed after accelerating aging of 300,000 turns, and the oxygen mass transfer resistance is significantly reduced, and the efficiency of the electrocatalytic reaction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581574A_ABST
    Figure CN119581574A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon loaded titanium nitride synergistic platinum-titanium alloy catalyst and a preparation method thereof. The preparation method comprises the following steps: mixing organic matter sol and titanium dioxide sol, and drying to obtain a precursor; calcining the precursor in an ammonia atmosphere to obtain titanium nitride doped porous carbon; stirring and mixing the titanium nitride doped porous carbon, a solvent and a platinum precursor, removing the solvent to obtain an intermediate, and calcining the intermediate in a protective gas atmosphere to obtain the porous carbon loaded titanium nitride synergistic platinum-titanium alloy catalyst. The catalyst prepared by the invention has a highly open porous structure and a high specific surface area, reduces the mass transfer resistance of oxygen, is beneficial to oxygen diffusion of an electro-catalytic reaction, and has very high catalytic activity; in addition, after the prepared catalyst is accelerated to age for 300,000 circles, the oxidation-reduction property of the catalyst is basically not changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst and a preparation method thereof. Background Art

[0002] Hydrogen fuel cells, methanol fuel cells and metal-air fuel cells are new energy conversion and storage devices that are expected to alleviate the energy crisis. (Abbreviation: oxygen reduction reaction) is a battery half-reaction in energy storage and conversion devices such as hydrogen fuel cells, alcohol fuel cells, and metal-air batteries. It occurs at the cathode of the battery. The process is that oxygen molecules obtain electrons, combine with protons or hydroxides, and are reduced to water. When the oxygen reduction reaction proceeds spontaneously, the reaction rate determined by chemical kinetics is very slow, so catalyst materials are needed to speed up the reaction.

[0003] Carbon-supported platinum catalyst materials, including carbon-supported platinum nanoparticles and carbon-supported platinum alloy nanoparticles, are relatively mature commercial materials that can efficiently catalyze oxygen reduction reactions and have been used in proton exchange membrane fuel cells, alcohol fuel cells, and metal-air batteries. However, the actual working environment of the above batteries is very harsh, generally containing oxygen and water, with temperature and electric fields, and the electrolyte is acidic or alkaline. Platinum or alloy nanoparticles supported on carbon have high surface energy. Under the influence of various factors during the working process, deactivation behaviors such as migration, agglomeration, sintering, growth, and dissolution will occur, resulting in a decrease in the activity of the catalyst material. At the same time, the oxygen reduction reaction is accompanied by the side reaction "Fenton reaction", which will produce strongly oxidizing intermediate species, oxidize platinum-based particles and carbon carriers, and also cause catalyst deactivation. Developing highly stable carbon-supported platinum catalyst materials by simultaneously inhibiting the deactivation of platinum-based particles and the oxidation of platinum and carbon carriers in the catalyst is a difficult problem that is currently being focused on in the field of fuel cells.

[0004] At present, there are three main reasons for the deactivation of carbon-supported platinum catalysts: (1) migration and growth of platinum particles, (2) dissolution and re-deposition of platinum particles, and (3) shedding of platinum particles caused by corrosion of carbon supports. All of the above three situations will cause a decrease in the activity of platinum catalysts. There are currently two main strategies to alleviate platinum deactivation. One is to enhance the interaction between platinum particles and supports to prevent the dissolution of platinum particles, and the other is to use non-carbon materials, such as transition metal nitrides, transition metal carbides and oxides and other corrosion-resistant materials. However, the actual situation is that the specific surface area and conductivity of these transition metal nitrides, carbides and oxides cannot be compared with those of carbon supports. Carbon-based and metal oxide-based coatings still have the disadvantages of not being resistant to oxidation and not resistant to electrochemical corrosion under acidic, aerobic, high humidity and high voltage conditions, while polymer-based coatings have low conductivity, which will reduce catalyst activity.

[0005] Therefore, simultaneously solving the problems of platinum particle deactivation and catalyst intolerance to oxidative corrosion remains a difficult problem that urgently needs to be solved in this field. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention loads a highly corrosion-resistant titanium nitride material on a carbon carrier, and then loads platinum particles. At the same time, titanium nitride can not only enhance the carrier metal interaction between it and the platinum particles to prevent the migration and agglomeration of the platinum particles, but also inhibit the dissolution and redeposition of the platinum particles. In addition, titanium nitride can also enhance the durability of the carbon carrier.

[0007] In order to achieve the above object, the present invention provides a method for preparing a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst. The organic sol and the titanium dioxide sol are mixed and dried to obtain a precursor; The precursor is placed in an ammonia atmosphere and calcined to obtain titanium nitride-doped porous carbon; The porous carbon doped with titanium nitride, a solvent and a platinum precursor are stirred and mixed, and then the solvent is removed to obtain an intermediate, and the intermediate is calcined under a protective gas atmosphere to obtain a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst.

[0008] Furthermore, the organic sol is obtained by dissolving an organic substance that can be solified in water in water or reacting an organic substance that can react in an aqueous environment to form a sol in water; wherein the organic substance that forms the sol is a polyhydroxybenzene compound or melamine and an aldehyde compound; The titanium dioxide sol is obtained by dispersing titanium-containing substances in water or alcohol.

[0009] In the present invention, the type of organic matter that can be solubilized in water does not need to be strictly limited. For example, it can be at least one of polyethylene glycol, methyl cellulose, ethyl cellulose, chitosan, gelatin, polyaniline, and polyimide. The polyhydroxybenzene compound includes any one of resorcinol, phenol, phloroglucinol, and catechol; the aldehyde compound includes at least one of formaldehyde, furfural, and the like.

[0010] In the present invention, the water in the organic sol and the water or alcohol in the titanium dioxide sol must be completely dried after mixing, so their volumes do not need to be strictly limited and can be selected according to needs. The organic sol and the titanium dioxide sol can be dried by any drying method including supercritical drying, freeze drying and atmospheric pressure drying after mixing.

[0011] Furthermore, the mass ratio of the organic matter that can be dissolved in water and can be sol-formed to the titanium-containing matter is 5-15:1-2; The mass ratio of the polyhydroxybenzene compound, the aldehyde compound and the titanium-containing substance is 3-8:5-10:1-2.

[0012] Furthermore, the titanium-containing material includes at least one of titanium dioxide, titanate, titanyl sulfate, and titanyl chloride.

[0013] Furthermore, the ammonia atmosphere calcination is specifically as follows: The temperature was raised to 600-1200°C at a heating rate of 2-10°C / min with an ammonia flow rate of 1-800 mL / min and kept at this temperature for 1-10 h.

[0014] Furthermore, the mass ratio of the titanium nitride-doped porous carbon, the solvent, and the platinum precursor is 0.3-1:20-50:0.1-0.3.

[0015] Furthermore, the solvent includes water or alcohol.

[0016] Preferably, the alcohol for dispersing the titanium-containing substance and the alcohol for dispersing the porous titanium nitride-doped platinum precursor are small molecule alcohols, which may be at least one of ethanol, n-propanol and isopropanol.

[0017] Furthermore, the calcination under a protective gas atmosphere specifically comprises: In a protective gas atmosphere, heat to 600-1200°C at a heating rate of 1-10°C / min and keep warm for 0.5-4h.

[0018] The protective gas atmosphere can be one of argon atmosphere, nitrogen atmosphere, helium atmosphere, hydrogen atmosphere and ammonia atmosphere, preferably hydrogen atmosphere.

[0019] In the present invention, the platinum precursor is a compound containing platinum element, and its type does not need to be strictly limited. For example, it can be at least one of chloroplatinic acid, platinum acetylacetonate, and platinum chloride. Preferably, the amount of platinum precursor added is controlled to have a mass fraction of platinum in the porous carbon-supported platinum alloy catalyst of 1%-60%. If the platinum content is low, the oxygen reduction activity of the final material will be low; if the platinum content is high, large-sized platinum nanoparticles will be formed during high-temperature heat treatment.

[0020] The present invention also provides a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst, which is obtained by using the above-mentioned preparation method of the porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst.

[0021] The present invention also provides the use of the porous carbon-supported titanium nitride in conjunction with the platinum-titanium alloy catalyst in a fuel cell. Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst of the present invention is relatively simple. Titanium nitride can eliminate the strong oxidizing free radicals generated by the "Fenton reaction" and protect the platinum alloy and the carbon carrier from being oxidized. At the same time, the titanium atoms in the titanium nitride on the surface of the platinum and carbon carrier can form a platinum-titanium alloy, and the titanium nitride can anchor the platinum alloy without agglomeration and migration. After 300,000 cycles of accelerated aging, the redox property of the prepared catalyst does not change substantially.

[0022] The catalyst prepared by the present invention has a highly open porous structure and a high specific surface area. The specific surface area of ​​the prepared catalyst is relatively high, and the pore size is mainly mesopores, but at the same time, the pore size distribution range is relatively wide, which can significantly reduce the mass transfer resistance of oxygen, is beneficial to the oxygen diffusion of the electrocatalytic reaction, and has a very high catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 A flow chart showing the preparation method of the porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst of the present invention; Figures 2(a), 2(b) and 2(c) respectively show transmission electron micrographs of the catalysts prepared in Example 1, Example 2 and Comparative Example 1, and Figure 2(d) shows a high-resolution transmission electron micrograph of the catalyst of Example 1; Figure 3 The XRD patterns of the catalysts prepared in Example 1, Example 2 and Comparative Example 1 are shown; Figure 4 shows the nitrogen adsorption-desorption curve of the catalyst prepared in Example 1; Figure 5 The pore size distribution curve of the catalyst prepared in Example 1 is shown; FIG6( a ) shows the linear sweep voltammetry curves of the catalysts prepared in Example 1, Example 2, Comparative Example 1, and commercial Pt / C, and FIG6( b ) shows the results of the accelerated durability test of Example 1. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0026] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1 like Figure 1 As shown, a method for preparing a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst comprises the following steps: The first step is to prepare an organosol A. 10 g of polyethylene glycol is weighed and dissolved in 30 mL of deionized water. The mixture is stirred until it is completely dissolved to form a uniform polyethylene glycol sol.

[0028] Step 2: Prepare titanium oxide sol B by dispersing 1 g of titanium dioxide powder with a particle size of 3-5 nm in 10 mL of deionized water.

[0029] Step 3: Prepare titanium oxide doped organic sol, mix the organic sol A prepared in the first step and the titanium oxide sol B prepared in the second step, stir evenly to obtain a mixture, and place the mixture in a heating device at 50° C. and let it stand until the mixture forms a uniform sol.

[0030] Step 4: freeze-dry the organic sol obtained in step 3 at a drying temperature of -80°C and a vacuum degree of 3Pa.

[0031] The fifth step is to prepare titanium nitride-doped porous carbon material. The organic sol prepared in the fourth step is placed in a cracking furnace. Under the protection of an ammonia atmosphere, ammonia gas is introduced at a flow rate of 400 mL / min. The temperature is increased to 900°C at a heating rate of 2°C / min, and the temperature is kept at this temperature for 2 hours. The titanium nitride-doped porous carbon material is obtained by cooling the furnace.

[0032] Step 6. Prepare porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst. Grind the titanium nitride-doped porous carbon material described in the fifth step into 200 mesh powder. Then, take 0.500 g of the powder and disperse it in 30 mL of water. Add 0.150 g of chloroplatinic acid nonahydrate, ultrasonicate for 15 min, stir for 18 h, and freeze-dry to obtain an aerosol-supported Pt precursor. Under a pure H2 protective atmosphere, heat to 1000 °C at a rate of 2 °C / min and keep warm for 0.5 h. Naturally cool to obtain a porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst.

[0033] Example 2 A method for preparing a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst comprises the following steps: The first step is to prepare an organosol A. 5 g of resorcinol is weighed and dissolved in 30 mL of deionized water and stirred until completely dissolved. Then 8 g of formaldehyde solution is added to form a uniform resorcinol formaldehyde sol.

[0034] Step 2: Prepare titanium oxide sol B by dispersing 1 g of titanium dioxide powder with a particle size of 3-5 nm in 10 mL of deionized water.

[0035] Step 3: Prepare titanium oxide doped organic sol, mix A prepared in the first step and B prepared in the second step, stir evenly to obtain a mixture, and place the mixture in a heating device at 50° C. and let it stand until the mixture forms a uniform sol.

[0036] Step 4: freeze-dry the organic sol obtained in step 3 at a drying temperature of -80°C and a vacuum degree of 3Pa.

[0037] The fifth step is to prepare titanium nitride-doped porous carbon material. The organic sol prepared in the fourth step is placed in a cracking furnace. Under the protection of an ammonia atmosphere, ammonia gas is introduced at a flow rate of 400 mL / min. The temperature is increased to 900°C at a heating rate of 2°C / min, and the temperature is kept at this temperature for 2 hours. The titanium nitride-doped porous carbon material is obtained by cooling the furnace.

[0038] Step 6. Prepare porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst. Grind the titanium nitride-doped porous carbon material described in the fifth step into 200 mesh powder. Disperse 0.500 g of the powder in 30 mL of water. Add 0.150 g of chloroplatinic acid nonahydrate. Ultrasonicate for 15 min. Stir for 18 h. Freeze-dry to obtain an aerosol-supported Pt precursor. Heat to 1000 °C at a rate of 2 °C / min under a pure H2 protective atmosphere and keep warm for 30 min. Cool naturally to obtain a porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst.

[0039] Comparative Example 1 A method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst, using commercial carbon carriers instead of organic sol to prepare porous carbon, comprising the following steps: The first step is to select 9g of commercial carbon carrier EC-300J and grind it into powder; The second step is to prepare titanium oxide sol by dispersing 1 g of titanium dioxide powder with a particle size of 3-5 nm in 10 mL of deionized water.

[0040] Step 3: Mix the ground EC-300J in Step 1 and the titanium oxide sol prepared in Step 2, stir evenly to obtain a mixture, and place the mixture in a heating device at 80°C and stir to evaporate water.

[0041] Step 4: freeze-dry the titanium oxide-doped EC-300J obtained in the third step at a drying temperature of -80°C and a vacuum degree of 3Pa.

[0042] The fifth step is to prepare titanium nitride-doped porous carbon material. The titanium oxide-doped EC-300J prepared in the fourth step is placed in a cracking furnace. Under the protection of an ammonia atmosphere, ammonia gas is introduced at a flow rate of 400 mL / min. The temperature is increased to 900°C at a heating rate of 2°C / min, and the temperature is kept at this temperature for 2 hours. The titanium nitride-doped porous carbon material is obtained by cooling the furnace.

[0043] Step 6. Prepare porous carbon-supported titanium nitride synergistic with platinum alloy catalyst. Grind the titanium nitride-doped EC-300J described in the fifth step into 200 mesh powder. Disperse 0.500 g of the powder in 30 mL of water. Add 0.150 g of chloroplatinic acid nonahydrate. Ultrasonicate for 15 min. Stir for 18 h. Freeze-dry to obtain an aerosol-supported Pt precursor. Heat to 1000 °C at a rate of 2 °C / min under a pure H2 protective atmosphere and keep warm for 30 min. Cool naturally to obtain a porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst.

[0044] Test Case The microscopic morphology of the catalysts prepared in Example 1, Example 2, and Comparative Example 1 was observed by transmission electron microscopy, and the results are shown in Figures 2 (a), 2 (b), and 2 (c), respectively. In these figures, the relatively fine black particles are platinum-titanium alloy particles, and their average particle size is less than 5nm. The lighter-colored areas are the prepared porous carbon, and the particles with a particle size of about 50nm on the surface of the porous carbon in the figure are titanium nitride particles. It can be seen from these figures that the distribution of platinum-titanium alloy particles in the catalyst prepared in Example 1 is the most uniform, which is conducive to the high activity of the catalyst; in addition, the titanium nitride particles on the surface of the porous carbon can anchor the platinum alloy to prevent it from agglomeration and migration. Figure 2 (d) also shows a high-resolution transmission electron microscopy image of the catalyst of Example 1. The lattice fringes on its surface are found to correspond to the (111) plane of the ordered Pt3Ti alloy and the (200) plane of titanium nitride, respectively, and the Pt3Ti alloy and titanium nitride are in contact, which is more conducive to the electron transfer during the oxygen reduction reaction (ORR), thereby improving the activity and stability of the catalyst.

[0045] The crystal structures of the catalysts prepared in Example 1, Example 2 and Comparative Example 1 were also observed using an X-ray diffractometer. Figure 3 shown. Figure 3 The diffraction peaks at 36.6°, 42.6°, 61.8°, 74° and 77.9° correspond to the (111), (200), (220), (311) and (222) crystal planes of titanium nitride, respectively, while the diffraction peaks at 22.9°, 32.6°, 40.1°, 46.6°, 52.4°, 57.9°, 67.9°, 72.6°, 77.1°, 81.7° and 86.2° correspond to the (100), (110), (111), (200), (210), (211), (220), (300), (310), (311) and (222) crystal planes of ordered Pt3Ti alloy, respectively, further illustrating the formation of titanium nitride and titanium-platinum alloy.

[0046] The surface area and pore size distribution of the catalyst of Example 1 were tested by nitrogen adsorption and desorption. The results are as follows: Figure 4 and Figure 5 The results show that the specific surface area of ​​the catalyst prepared in Example 1 is as high as 411m 2 / g, and the pore size is mainly mesopores. At the same time, the pore size distribution range is relatively wide, which can significantly reduce the mass transfer resistance of oxygen and is beneficial to the oxygen diffusion of the electrocatalytic reaction.

[0047] In order to test the ORR activity of the catalysts of the embodiments and comparative examples, a linear sweep voltammetry test was performed in a 0.10 mol / L perchloric acid aqueous solution, and the results are shown in FIG6 (a). It can be seen that the half-wave potentials of the catalysts of the embodiments and comparative examples of the present invention are higher than that of commercial Pt / C. In particular, the half-wave potential of the catalyst of Example 1 is as high as 0.9 V, and its mass activity reaches 0.35 mA / mgPt. The catalyst of Example 1 was also subjected to an accelerated durability test at a voltage between 0.6 V and 1.0 V in an oxygen atmosphere. As shown in FIG6 (b), after 300,000 cycles, its half-wave potential only dropped by 2 mV, showing good durability, which is higher than the level reported in most existing literature, confirming that the porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst proposed in the present invention has strong catalytic activity and durability.

[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst, characterized in that: include, The organic sol and the titanium dioxide sol are mixed and dried to obtain a precursor; The precursor is placed in an ammonia atmosphere and calcined to obtain titanium nitride-doped porous carbon; The porous carbon doped with titanium nitride, a solvent and a platinum precursor are stirred and mixed, and then the solvent is removed to obtain an intermediate, and the intermediate is calcined under a protective gas atmosphere to obtain a porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst.

2. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 1, characterized in that: The organic sol is obtained by dissolving an organic substance that can be solified in water in water or reacting an organic substance that can react in an aqueous environment to form a sol in water; wherein the organic substance that forms the sol is a polyhydroxybenzene compound or melamine and an aldehyde compound; The titanium dioxide sol is obtained by dispersing titanium-containing substances in water or alcohol.

3. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 2, characterized in that: The mass ratio of the organic matter that can be dissolved in water and can be sol-formed to the titanium-containing matter is 5-15:1-2; The mass ratio of the polyhydroxybenzene compound or melamine, aldehyde compound and titanium-containing substance is 3-8:5-10:1-2.

4. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 2, characterized in that: The titanium-containing material includes at least one of titanium dioxide, titanate, titanyl sulfate and titanyl chloride.

5. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 1, characterized in that: The ammonia atmosphere calcination is specifically as follows: The temperature was raised to 600-1200°C at a heating rate of 2-10°C / min with an ammonia flow rate of 1-800 mL / min and kept at this temperature for 1-10 h.

6. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 1, characterized in that: The mass ratio of the titanium nitride-doped porous carbon, the solvent and the platinum precursor is 0.3-1:20-50:0.1-0.

3.

7. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 1, characterized in that: The solvent includes water or alcohol.

8. The method for preparing porous carbon-supported titanium nitride synergistic with platinum-titanium alloy catalyst according to claim 1, characterized in that: The calcination under a protective gas atmosphere specifically comprises: In a protective gas atmosphere, heat to 600-1200°C at a heating rate of 1-10°C / min and keep warm for 0.5-4h.

9. A porous carbon-supported titanium nitride synergistic platinum-titanium alloy catalyst, characterized in that: The catalyst is obtained by using the method for preparing the porous carbon-supported titanium nitride synergistic with the platinum-titanium alloy catalyst as described in any one of claims 1 to 8.

10. Use of the porous carbon-supported titanium nitride in conjunction with a platinum-titanium alloy catalyst as claimed in claim 9 in a fuel cell.

Citation Information

Patent Citations

  • Low-platinum catalyst based on nitride nano particle and preparation method of low-platinum catalyst

    CN105032460A

  • Titanium nitride hybridization carbon composite material and preparation method thereof

    CN110368978A

  • Modified platinum alloy catalyst as well as preparation method and application thereof

    CN118610499A